The Epistemology Behind the Educational Philosophy of Montessori: Senses, Concepts, and Choice - Colgan, Andrew D. (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2016)
This article seeks to re-introduce Dr. Maria Montessori’s educational philosophy, which has been absent from modern philosophy of education literature. It describes and analyzes crucial aspects of her epistemology, as best known through her Method. Discussed are the need for early education, the development of the senses, and the exercise of choice by the students. Concept formation is also shown to be an important part of Montessori’s philosophy of instruction. This article concludes with a brief resolution of the “is–ought” objection as framed by Scheffler that might be waged against Montessori’s approach.